The dresses of the Miss by Galdino Lenzi:analysis of clothing collections to comprehend the manufacture and consumption of fashion in the 1970s in Santa Catarina (ModaPalavra e-periódico, 2015)
The article presents the results of a research project that aimed to examine three dresses belonging to the clothing collection of UNIVALI, made by Galdino Lenzi, a fashion designer from Santa Catarina, for Miss Brusque and Santa Catarinain 1976. To make the investigations, we used specific methodology for analysis of historical documents under the material culture, as proposed by Sant'Anna et. al. (2009). Considering these garments as objects / document, the observations made possible the understanding of certain cultural, social and historical aspects of a period and region, as well as the appreciation of employed techniques in the manufacture of fashion products in the 1970s, allowing the access to information that enable the development of new fashion design products.
Keywords: material culture; the fashion history; the 1970s